Epilepsy—Work-Up and Management in Children - Tenney, Jeffrey R. (Seminars in Neurology, 2020)
Pediatric epilepsy is a highly variable condition due to age-related expression of syndromes that require specific diagnosis, evaluations, and treatments. Children with epilepsy differ from their adult counterparts in many important ways, mostly related to the age-related expression of specific epilepsy syndromes. This results in many important considerations related to the epilepsy diagnosis, classification, evaluations to determine an etiology, as well as treatment guidelines. A good understanding of these factors will help to establish an accurate epilepsy diagnosis, which in turn will guide appropriate testing and treatment decisions. In this way, patients will have improved seizure outcomes, and families will be educated appropriately and provided with the most accurate prognostic information available. The purpose of this article is to review the diagnosis, work-up, and management of pediatric epilepsy.
Keywords: epilepsy; pediatrics; management; work-up